A influência da variação da composição e pressão nas ligas Al-Fe E Al-Fe-Si solidificadas sob pressão: taxa de resfriamento microestrutura, resistência mecânica e corrosão - Lima, Robson Andrade de (2019)
Squeeze Casting is a process that involves pouring a liquid material and introducing a pressure into the system, it is one of the casting processes that can result in the highest attainable mechanical properties. The objective of this work is to analyze the influence of the cooling rate and pressure for the solidification process under pressure in the al-Fe alloys and Al-Fe-Si ternary alloys, and to correlate with the microstructure, Vickers hardness, tensile strength and corrosion. The cooling curves were obtained with the experimental mapping through thermocouples duly inserted in both the metal and the mold, through these data we can trace the curves of the thermal profiles and cooling rates in the solidification under pressure. The experiment was carried out with the dilute aluminum alloy iron alloys with the following Al-1% Fe compositions; Al-1.5% Fe, Al-1.8% Fe and the ternary alloy Al-1.0% Fe-1.0% Si with pressures ranging from ambient to 50, 100 and 150 MPa. Afterwards, microstructural tests, Vickers microhardness, tensile strength and corrosion tests were carried out, in which the results obtained showed in general that a decrease in defects, an increase in the cooling rate, an increase in the tensile strength, an increase in the corrosion process, as well as a basically cellular structure corroborating some works of Al- Fe hypoeutetic alloys.